If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 33) = 222 Reorder the terms: 6(33 + x) = 222 (33 * 6 + x * 6) = 222 (198 + 6x) = 222 Solving 198 + 6x = 222 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-198' to each side of the equation. 198 + -198 + 6x = 222 + -198 Combine like terms: 198 + -198 = 0 0 + 6x = 222 + -198 6x = 222 + -198 Combine like terms: 222 + -198 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 65x=55(x+15) | | 1+8x-8x=-10 | | X/9-8=7 | | C=1+9 | | (-2)+x=0 | | -4(3n+8)=8(n+1) | | 4*(50+x)+3800*(50+2x)=6.13 | | 7(-2x+4)+6=7x-21 | | 4*(50+x)+3800*(50+2x)=6.13whatisx | | 3n+m= | | 10x+6-(3x-3)-(3x-3)= | | X=X+273 | | 5-/y-13/ | | 21b-13=29 | | 21b-13=19 | | 5(2x+6)=4(-5-2x+3x) | | 10x+5=-15 | | 1+8x-8=-10 | | 1/2(n-4)=16 | | X=2(10-x) | | 10*x=6*(3+x) | | x-37/9=7 | | 5.8-2.9-7.8= | | 4*(50+x)+3800*(50+2x)= | | 2(X+1)+2(X+1)=24whatisX | | -5(m+8)=-2(m+8) | | -4=x-3/2 | | 3-2y-1=4y-7 | | 4x-18=9x+6 | | -9(4-x)-(1+7x)=-25 | | X+3y+27=0 | | 3/4×4= |